The Effects of Synthetic Estrogen Exposure on the Sexually Dimorphic Liver Transcriptome of the Sex-Role-Reversed Gulf Pipefish. - Emily Rose; Sarah P Flanagan; Adam G Jones (PLoS ONE, 2015)
Species exhibiting sex-role reversal provide an unusual perspective on the evolution of sex roles and sex differences. However, the proximate effects of sex-role reversal are largely unknown. Endocrine disruptors provide an experimental mechanism to address hormonal regulation of sexually dimorphic gene expression in sex-role-reversed taxa. Here, we investigate gene expression patterns in the liver of the sex-role-reversed Gulf pipefish, because the liver is known to be sexually dimorphic and estrogen-regulated in species with conventional sex roles. Using next-generation RNA-sequencing technology (RNA-seq), we detected sexually dimorphic hepatic gene expression patterns, with a total of 482 differentially expressed genes between the sexes in Gulf pipefish. Two-thirds of these genes were over-expressed in females, and the sex-specific transcriptomes of this sex-role-reversed pipefish's liver were superficially similar to those of fishes with conventional sex-roles. We exposed females, pregnant males, and non-pregnant males to 17α-ethinylestradiol (EE2) at ecologically relevant concentrations of 5ng/L and compared gene expression patterns in the livers of exposed fish to control fish. Several genes that were up-regulated in EE2-exposed males relative to control males were also found to be female-biased in control animals. These genes included several of the classic estrogen biomarkers, such as vitellogenin, choriogenin, and zona pellucida. Thus, estrogen exposure induced feminization of the male liver transcriptome in a sex-role-reversed pipefish. These results suggest that the ancestral state of estrogen-regulated female reproductive physiology has been retained in all sex-role-reversed vertebrates thus far studied, despite substantial evolution of the hormonal regulation of ornamentation and mating behavior in these interesting taxa.